FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA GENERASI Z DAN GENERASI MILENIAL DI INDONESIA TERHADAP ZARA - Andres Dharma Nurhalim (STIE Wiyatamandala, 2022)
The purpose of this study aims to analyze the factors that influence purchasing decisions in generation z and millennial generations in Indonesia against Zara.The analytical method used by the author in conducting this research is to use quantitative research with a total population of 83 respondents, which areconsumers who have bought Zara. In collecting the data, it was done by distributing questionnaires in which there were several statements. In this study,the variables were divided into several parts, including price (X1), product quality (X2) and brand image (X3) as independent variables, and purchasing decisions (Y) as the dependent variable. To measure the magnitude of the influence on these variables, the authors use the method of multiple regression analysis. From the results of the analysis, it is found that there is a significant and simultaneous influence on the variables of price, product quality and brand image onpurchasing decisions at Zara in Indonesia.